2013
DOI: 10.1111/cas.12274
|View full text |Cite
|
Sign up to set email alerts
|

Phase II feasibility study of preoperative chemotherapy with docetaxel, cisplatin, and fluorouracil for esophageal squamous cell carcinoma

Abstract: The combination of docetaxel, cisplatin, and 5-fluorouracil (DCF) as preoperative treatment for esophageal squamous cell carcinoma (ESCC) has not been investigated. We carried out a multicenter phase II feasibility study of preoperative chemotherapy with DCF for ESCC. Patients with clinical stage II ⁄ III ESCC (International Union Against Cancer TNM classification system, 6th edition) were eligible. Chemotherapy consisted of i.v. docetaxel (70-75 mg ⁄ m 2 ) and cisplatin (70-75 mg ⁄ m 2 ) on day 1, and continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
149
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 18 publications
7
149
8
Order By: Relevance
“…Recently developed chemotherapy strategies have improved the outcomes of patients with ESCC (3)(4)(5). Although the DCF regimen results in favorable clinical responses in ESCC, cisplatin frequently induces AKI (2,5,6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently developed chemotherapy strategies have improved the outcomes of patients with ESCC (3)(4)(5). Although the DCF regimen results in favorable clinical responses in ESCC, cisplatin frequently induces AKI (2,5,6).…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of systemic chemotherapy, including the combination of docetaxel, cisplatin and 5-fluorouracil (DCF), has improved long-term outcomes in patients with ESCC (3)(4)(5). Although the DCF regimen was expected to yield a high response rate in ESCC, the approach frequently results in severe adverse events such as acute kidney injury (AKI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hara et al reported a high response rate from triplet chemotherapy using CDDP, 5-FU, and docetaxel (DCF) and this could be another treatment option. 38) In the phase II trial, treatment completion rate was 90.5% and clinical response rate was 64.3% and pathological complete response was observed in 17%. For adverse events, neutropenia (≥ Grade 3) was observed in 83% of patients but there were no cases of treatment related deaths.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 97%
“…[52][53][54][55][56][57] Nomura et al 56) reported that the overall response rate was significantly higher in the DCF group than in the CF group in patients with clinical stage III or T3 esophageal SCC. After propensity score matching, the improvement in OS in the DCF group reached statistical significance (p = 0.05).…”
Section: Neoadjuvant and Adjuvant Chemotherapymentioning
confidence: 99%